Autoimmune disease and gender: Plausible mechanisms for the female predominance of autoimmunity (2012)
A large number of autoimmune diseases (ADs) are more prevalent in women. The more frequent the AD and the later it appears, the more women are affected. Many ideas mainly based on hormonal and genetic factors that influence the autoimmune systems of females and males differently, have been proposed to explain this predominance. These hypotheses have gained credence mostly because many of these diseases appear or fluctuate when there are hormonal changes such as in late adolescence and pregnancy. Differences in X chromosome characteristics between men and women with an AD have led researchers to think that the genetic background of this group of diseases also relates to the genetic determinants of gender. These hormonal changes as well as the genetic factors that could explain why women are more prone to develop ADs are herein reviewed. © 2011 Elsevier Ltd.